(untitled) (Global Journal of Science Frontier Research, 2019)
Twenty-first century Theoretical Physics is undergoing a major ’Paradigmatic-Shift’ from the old ’Material-Causal’ Paradigm underlying both Relativity Theory (RT) and Quantum Mechanics (QM) to the New ’Computational Unified Field Theory’s (CUFT) ’A-Causal Computation’ (ACC) Paradigm’; The ACC Paradigm has been shown capable of replicating all major RT & QM laws and phenomena, while challenging and revising key assumptions of the old ’Material-Causal’ Paradigm including:the "Big-Bang" Model, RT’s "Einstein’s Equations", the "Second Law of Thermodynamics", the possibility of "Time-Reversal" and transcending the "Speed of Light" barrier, etc. Initial empirical validation for the CUFT’s new ACC Paradigm was given through the "Proton-Radius Puzzle" associated findings. This article sets to test directly two "time-sensitive" "critical -predictions" of the CUFT involving a Cosmological measurement of the "Non-Continuous Accelerated Expansion of the Universe" (NCAEU) predicted to occur around the Jewish "Rosh Hashanna" (New Year) due to the postulated effect of a "Collective Human Consciousness Focus" (CHCF) upon the CUFT’s discovered "Universal Computational/ Consciousness Principle" (UCP) which computes every exhaustive spatial pixel in the universe at the incredible rate of "c 2 /h" = 1.36 -50 sec’!; and a Subatomic Accelerator "Fine-Temporal Measurement" (FTM) of the CUFT’s predicted greater number of times that a relatively "more massive" Muon particle would be detected than a "less-massive" electron particle across a given number of such FTM.